2008
DOI: 10.1021/cm801036k
|View full text |Cite
|
Sign up to set email alerts
|

On the Energetic Stability and Electrochemistry of Li2MnSiO4 Polymorphs

Abstract: The thermodynamic stability of Li 2 MnSiO 4 polymorphs and their electrochemical properties as electrode for Li batteries are investigated combining experimental and computational methods. Three possible Li 2 MnSiO 4 forms have been considered crystallizing in Pmnb, Pmn2 1 (β-Li 3 PO 4 derivatives) and P2 1 /n (γ-Li 3 PO 4 derivative) space groups (S.G.). We have first demonstrated that the relative stability of βand γ-Li 3 PO 4 polymorphs is well-reproduced by density functional theory (DFT) methods (LDA, GGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
180
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(204 citation statements)
references
References 28 publications
22
180
1
1
Order By: Relevance
“…The reason for observed differences in QS values is not fully understood, however we presume this difference can be ascribed to the different polymorph used in our experiment as it was used by Nyten. It is worth to mention that the existence of different polymorphs in Li 2 FeSiO 4 was not proven yet, however the above opinion is based on the work on Li 2 MnSiO 4 and Li 2 CoSiO 4 [2,3,12,20]. Based on our in-situ Mössbauer experiment we agree with a conclusion given by Nyten [7], that local environment of iron observed with Mössbauer spectroscopy is very similar before and after "phase transition" reflected as a shift of potential from 3.1 to 2.8 V. At the end of Mössbauer part we need to emphasize that Mössbauer parameters of the magnetic phase remain very similar during the oxidation/reduction process in all fitted spectra.…”
Section: Xrd and Mössbauer Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for observed differences in QS values is not fully understood, however we presume this difference can be ascribed to the different polymorph used in our experiment as it was used by Nyten. It is worth to mention that the existence of different polymorphs in Li 2 FeSiO 4 was not proven yet, however the above opinion is based on the work on Li 2 MnSiO 4 and Li 2 CoSiO 4 [2,3,12,20]. Based on our in-situ Mössbauer experiment we agree with a conclusion given by Nyten [7], that local environment of iron observed with Mössbauer spectroscopy is very similar before and after "phase transition" reflected as a shift of potential from 3.1 to 2.8 V. At the end of Mössbauer part we need to emphasize that Mössbauer parameters of the magnetic phase remain very similar during the oxidation/reduction process in all fitted spectra.…”
Section: Xrd and Mössbauer Analysismentioning
confidence: 99%
“…As-prepared samples are usually mixtures of polymorphs due to small difference in formation energy. Some polymorphs, however, can be isolated with selective synthesis conditions [12]. Although Li 2 FeSiO 4 and Li 2 MnSiO 4 are iso-structural, their electrochemical activities are different [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, LM2 with 20 wt % of acetylene black shows a superior electrochemical stability and a higher rate capability as compared to those reported so far. [15][16][17][18][19] Because the electrical conductivity of Li 2 MnSiO 4 is very low, almost in the insulator range, it is expected that a large impedance would develop at the cathode-electrolyte interface that would hinder the electrochemical intercalation of Li during charge-discharge. The impedance spectra of the cells LM0 and LM2 have been recorded at various stages, before any charge-discharge and during cycling after 10 and 20 cycles.…”
Section: A678mentioning
confidence: 99%
“…The relationship of crystal structure and electrochemical performance has been investigated by theoretical calculation. Arroyo-deDompablo's group [41] reported that the calculated average 2Li + intercalation potentials are 4.18, 4.19, and 4.08 V for Pmnb, Pmn2 1 , and P2 1 /n, respectively. Fisher et al [39] demonstrated that the orthorhombic Pmn2 1 phase possesses the lowest Li + migration energy barrier among the four phases.…”
Section: Mnsiomentioning
confidence: 99%